2022
DOI: 10.1039/d2ta04073e
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative selective benzyl alcohol oxidation and hydrogen production over Pd6(SC12H25)12cluster-coupled CdS nanorods: the key role of water in photocatalytic benzyl alcohol splitting

Abstract: Photocatalytic splitting of alcohols into hydrogen and corresponding carbonyl compounds has potential applications in the production of clean H2 fuel and high-value chemicals using solar light as the sole energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Subsequently, the cleavage of O‐H bonds occurs with the reaction of *C 6 H 5 CH 2 OH → *C 6 H 5 CH 2 O − (*BA1) + H + proceeds, which exhibits the highest free energy barrier, and is thus considered as the rate‐determining step (RDS) of the reaction. [ 29 ] Finally, with the breakage of C α ‐H bonds, another H + is further lost, forming C 6 H 5 CHO. For the above process, the free energy barrier of RDS for BiOCl MSCN is apparently lower than BiOCl NS‐1 (2.52 eV), only 2.13 eV, revealing the presence of oxygen vacancies is more thermodynamically favorable for BA oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the cleavage of O‐H bonds occurs with the reaction of *C 6 H 5 CH 2 OH → *C 6 H 5 CH 2 O − (*BA1) + H + proceeds, which exhibits the highest free energy barrier, and is thus considered as the rate‐determining step (RDS) of the reaction. [ 29 ] Finally, with the breakage of C α ‐H bonds, another H + is further lost, forming C 6 H 5 CHO. For the above process, the free energy barrier of RDS for BiOCl MSCN is apparently lower than BiOCl NS‐1 (2.52 eV), only 2.13 eV, revealing the presence of oxygen vacancies is more thermodynamically favorable for BA oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Femtosecond Time-Resolved Transient Absorption Spectroscopy: The femtosecond pump-probe transient absorption (TA) spectrometer based on a 1 KHz Ti: sapphire laser amplification system (Spitfire Ace, Spectra Physics) was described elsewhere. [23,24] Briefly, a portion of the output beam with a center wavelength of 800 nm and a pulse width of 80 fs from the amplifier was guided into an optical parametric amplification system (TOPAS Prime, Light Conversion) to produce the femtosecond pump beam with tunable wavelength, while another part of the laser beam was focused into a CaF 2 crystal to generate the white light continuum (350-700 nm) to serve as the probe beam. The pump (360 nm, 200 nJ per pulse) and probe beams overlapped in a 2 mm fused silica cuvette where the samples were dispersed in water at a concentration of 0.5 mg mL −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The deposition of secondary components such as cocatalysts and heterojunction formation allow the photoreforming selectivity to be tuned to favor the generation of aldehydes or C–C coupling products. Numerous types of photocatalysis have been developed for the highly selective formation of aldehydes, with recent high-efficiency photocatalysts achieving selectivity of ≥90%. The hydrogen generated when photocatalysts are used for benzyl alcohol conversion is also favorable; for example, Hao et al developed nickel-sulfide-decorated zinc sulfide nanorods for the photocatalytic transformation of benzyl alcohol to benzaldehyde coupled with H 2 evolution …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that the oxidative ability of the catalyst is primarily enhanced via the use of cocatalyst systems, which improve transformation efficiency and selectivity. …”
Section: Introductionmentioning
confidence: 99%